Personal competency assessment in the performance at central hospital Medical office, Bangkok - Phol-in, Pisit (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
In this thesis, the researcher determines (1) competency assessment of person performance at central hospital, Medical office, Bangkok (2) to compare the performance of person at the central hospital by personal characteristics (3) to study obstacles on the performance of person at central hospital, Medical office, Bangkok (4) to study guideline for development of personal performance practice at central hospital, Medical office, Bangkok. The population in this study includes government officer, employees, temporary employees and employee’s social security at central hospital, Medical office, Bangkok consists of 876 employees but not include physician, nurse and daily worker. Researcher selected sampling technique by using accidental sampling by random selection of samples of 275 people. As an instrument of research, the researcher develop the questionnaire by review the documents with relevant research and applied competency study by Office of the Civil Service to evaluate and competency assessment at the central hospital, Bangkok. Before sending the questionnaire, 3 expertise evaluated questionnaire to collect the grammar consider content validity and reliability using cronbach alpha between 0.70 – 0.92. In carrying out the quantitative research, the analyzed statistics using percentage, mean, standard deviation, T test and one-way ANOVA. In the course of analyzing the researcher found the level of competency assessment of person at central hospital, Medicinal office, Bangkok found that overall evaluated is very good (mean 3.96) the level of assessment practices sort 3 respectively: ethical, commitment and service quality. Problems on the performance of personnel at central hospital, Medical office, Bangkok in the terms of good service found that overall evaluated is less (mean 2.41) the level of assessment practices sort 3 respectively: lack of motivation to practice, environment unfavorable to service agencies and lack of control over the service. Solutions from respondent recommend that should be adjusted to the new working system by the system to suit the individual, contributing to the development of workload performance, set vision mission of each agency in accordance with the vision and mission of the Central hospital in the psychiatric services, creating an atmosphere of working in cooperation with each other. Compare the performance of individuals in the hospital by personal characteristics showed that the performance of the personnel in the hospital were not significantly different statistically. With retail analyst, found that age affects the ethical performance. And education affects the good service. Article history : Accepted 5 May 2014 SIMILARITY INDEX = 1.14